2021
DOI: 10.1136/bmjopen-2020-041794
|View full text |Cite
|
Sign up to set email alerts
|

Views and experiences of people with acne vulgaris and healthcare professionals about treatments: systematic review and thematic synthesis of qualitative research

Abstract: ObjectivesThe objective of this study was to systematically review and synthesise qualitative papers exploring views and experiences of acne and its treatments among people with acne, their carers and healthcare professionals (HCPs).DesignSystematic review and synthesis of qualitative papers.MethodsPapers were identified through Medline, EMBASE, PubMed, PsychINFO and CINAHL on 05 November 2019, forward and backward citation searching, Google Scholar and contacting authors. Inclusion criteria were studies repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 36 publications
2
37
0
1
Order By: Relevance
“…Acne is the most common chronic inflammatory disease of hair follicles and sebaceous glands in adolescents and adults. Studies showed that about 80% of people over 20 years old had ever suffered from acne (1,2), and about 95% of acne patients would have acne scars of varying degrees (3). Facial atrophic scars can cause damage to the patient's appearance, often adversely affect the patient's social activities and mental health, and seriously affect the patient's quality of life (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Acne is the most common chronic inflammatory disease of hair follicles and sebaceous glands in adolescents and adults. Studies showed that about 80% of people over 20 years old had ever suffered from acne (1,2), and about 95% of acne patients would have acne scars of varying degrees (3). Facial atrophic scars can cause damage to the patient's appearance, often adversely affect the patient's social activities and mental health, and seriously affect the patient's quality of life (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of conclusive evidence, 9 many patients believe their acne is related to diet, lack of face washing, or sun exposure. 10 Topical combination products should be trialed for 2 to 3 months before trying other treatments.…”
Section: Methodsmentioning
confidence: 99%
“…In UK, a study investigated the psychological sequelae of acne and assessed the participants help-seeking behaviors found a significant correlation between the severity of acne and CADI, moreover, the feeling of embarrassment and unsuitable schedules were observed as obstacles to help seeking among young adults [17]. In a systematic review carried out by Athena et al, found that myths and misconceptions regarding causes of acne do exist, and poor experience between the patient and health care provider with the latter not recognizing the magnitude of psychological impact of acne may lead to misperception and self-blame [18]. Furthermore, including the family members in the management and encouraging their support have shown a positive impact and did improve the experience and make it less uncomfortable [18].…”
Section: Burdenmentioning
confidence: 99%
“…In a systematic review carried out by Athena et al, found that myths and misconceptions regarding causes of acne do exist, and poor experience between the patient and health care provider with the latter not recognizing the magnitude of psychological impact of acne may lead to misperception and self-blame [18]. Furthermore, including the family members in the management and encouraging their support have shown a positive impact and did improve the experience and make it less uncomfortable [18].…”
Section: Burdenmentioning
confidence: 99%